Generative AI and Algorithmic Art: Disrupting the Framing of Meaning and Rethinking the Subject-Object Dilemma (Global Journal of Computer Science and Technology, 2023)
In the revision of treatments of contemporary art in the 21st century art historians are recognizing 2022 as the dawn of the age of creative artificial intelligence AI The emergence of generative AI tools like ChatGPT and Stable Diffusion in late 2022 immediately disrupted the established practices of the art world leading to debates about the validity of AI Art and the emergence of a new market for NFTs However fears regarding the death of the artist are unwarranted when considering the historical adoption of new technologies by artists such as photography The role of the artist will undoubtedly transform and the definition of art will be redefined once again To better understand how AI generative art will impact traditional art- making practices this study will present an AI generative art development pipeline and provide recommendations for future technical and theoretical considerations of the subject-object dilemma in art through a poststructuralist reading of reception theory While the ways in which artists will utilize these new tools are currently uncertain this paper will explore one potential workflow in which content created via text-to-image prompts in Astra ai is exported to Stable Diffusion Through an evaluation of this process and the introduction of new steps for artists using AI generative content recommendations will be provided for both the creation and interpretation of human-AI collaborative and co-creative processes and content
Keywords: artificial intelligence; creative process; generative AI; Co-creativity; human-AI creativity